Factors Associated with Providers' Work Engagement and Burnout in Homeless Services: A Cross‐national Study. Issue 1 (2nd November 2020) - Lenzi, Michela; Santinello, Massimo; Gaboardi, Marta; Disperati, Francesca; Vieno, Alessio; Calcagnì, Antonio; Greenwood, Ronni Michelle; Rogowska, Aleksandra M.; Wolf, Judith R.; Loubière, Sandrine; Beijer, Ulla; Bernad, Roberto; et al.
Abstract: The complexity of homeless service users' characteristics and the contextual challenges faced by services can make the experience of working with people in homelessness stressful and can put providers' well‐being at risk. In the current study, we investigated the association between service characteristics (i.e., the availability of training and supervision and the capability‐fostering approach) and social service providers' work engagement and burnout. The study involved 497 social service providers working in homeless services in eight different European countries (62% women; mean age = 40.73, SD = 10.45) and was part of the Horizon 2020 European study "Homelessness as Unfairness (HOME_EU)." Using hierarchical linear modeling (HLM), findings showed that the availability of training and supervision were positively associated with providers' work engagement and negatively associated with burnout. However, results varied based on the perceived usefulness of the training and supervision provided within the service and the specific outcome considered. The most consistent finding was the association between the degree to which a service promotes users' capabilities and all the aspects of providers' well‐being analyzed. Results are discussed in relation to their implications for how configuration of homeless services can promote social service providers' well‐being and high‐quality care. Highlights: The complexity of users' characteristics can make working with homeless people very stressful. Some features of homeless services are likely to be associated with providers' well‐being. Useful training was associated with higher levels of work engagement and lower levels of burnout. Non useful supervision was positively associated with providers' burnout. Capability‐fostering approach was positively associated with providers' well‐being.